2020
DOI: 10.3389/fmed.2020.00178
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling Reveals Indoxyl Sulfate Should Be Culpable of Impaired T Cell Function in Chronic Kidney Disease

Abstract: Introduction: Chronic inflammation and immune system dysfunction have been evaluated as major factors in the pathogenesis of chronic kidney disease (CKD), contributing to the high mortality rates observed in these populations. Uremic toxins seem to be the potential "missing link." Indoxyl sulfate (IS) is one of the protein-bound renal toxins. It participates in multiple pathologies of CKD complications, yet its effect on immune cell has not been studied. This study aimed to explore the genome-wide expression p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…As an antigenpresenting cell, dendritic cells would induce T cell proliferation and migration to inspire the immune response [185]. T cells, especially CD4 + -T cells, are an important source to persist inflammation in CKD patients [16,186,187]. Abnormal activation of T cells leads to a release of proinflammatory cytokines such as TNF-α and IFN-γ [186], which play an important role in the recruitment of BMSCs [138][139][140].…”
Section: Local Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…As an antigenpresenting cell, dendritic cells would induce T cell proliferation and migration to inspire the immune response [185]. T cells, especially CD4 + -T cells, are an important source to persist inflammation in CKD patients [16,186,187]. Abnormal activation of T cells leads to a release of proinflammatory cytokines such as TNF-α and IFN-γ [186], which play an important role in the recruitment of BMSCs [138][139][140].…”
Section: Local Immune Responsementioning
confidence: 99%
“…T cells, especially CD4 + -T cells, are an important source to persist inflammation in CKD patients [16,186,187]. Abnormal activation of T cells leads to a release of proinflammatory cytokines such as TNF-α and IFN-γ [186], which play an important role in the recruitment of BMSCs [138][139][140]. B cells may also play a role in kidney injury.…”
Section: Local Immune Responsementioning
confidence: 99%
“…It has been reported that the serum levels of IP-10 and IL-8 in diabetic patients are higher than in healthy subjects [58,59]. In addition, research revealed that CXCL10 and CXCL8 are generated by stimulation with the uremic toxin IS [6,60]. In our investigation, mRNA and protein levels of CXCL10 and CXCL8 in HUVECs overexpressing lnc-SLC15A1-1 were escalated and actively secreted to the extracellular space as proteins significantly increased in conditioned medium (Figure 5E,F).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has indicated that the immunopathological and inflammatory cascades play an important role in the initiation and development of CVD [2]. Chronic inflammation and immune system dysfunction are characteristic of DM and can produce a plethora of cytokines and chemokines, thereby contributing to CVD events [3][4][5][6]. For example, IP-10, encoded by CXCL10, and IL-8, encoded by CXCL8, belong to the C-X-C chemokine subfamily [7], and the literature is overflowing with evidence regarding their potential roles in causing atherosclerosis [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…AST-120 has been found by other researchers to significantly decrease CD8 + T cells (-33.9% for central memory T cells, and -42.6% for CD8 + naïve T cells), but it does not affect or slightly reduce CD4 + T cells (0 for T helper cell number, and -13.1% for early activated CD4 + T cells) 36 , which are consistent with our findings in this study. The reduced uremic toxins, such as indoxyl sulfate and p-cresyl sulfate, maybe involved in the phenomenon 37 - 40 . However, the exact mechanism of AST-120 exerting its anti-CKD effect still needs further study.…”
Section: Discussionmentioning
confidence: 99%